2014
DOI: 10.1139/bcb-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HDAC increases the senescence induced by natural polyphenols in glioma cells

Abstract: Cellular senescence is an irreversible block of cellular division, and induction of senescence is being considered for treatment of many cancer types, mainly those resistant to classical pro-apoptotic therapies. Resveratrol (Rsv) and quercetin (Quer), two natural polyphenols, are able to induce senescence in different cancer models, including gliomas, the most common and aggressive primary brain tumor. These polyphenols modulate the activity of several proteins involved in cell growth and death in cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…The basis for normal breast cell resistance to HDACis is not fully understood, although cancer cells with multiple defects cannot reverse the critical effects of HDACis similar to normal cells. 44, 45 This resistance of normal breast cells presumably functions to avoid the autoimmunity caused by treatment with HDACis. Taken together, our study indicates that BC patients who receive HDACi treatment might show increased immune activation in addition to tumor cell inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The basis for normal breast cell resistance to HDACis is not fully understood, although cancer cells with multiple defects cannot reverse the critical effects of HDACis similar to normal cells. 44, 45 This resistance of normal breast cells presumably functions to avoid the autoimmunity caused by treatment with HDACis. Taken together, our study indicates that BC patients who receive HDACi treatment might show increased immune activation in addition to tumor cell inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Inducing senescence—a quiescent, non‐dividing cell state—in cancerous cells is a desired outcome for cancer therapy, and a number of studies have shown HDAC inhibitors to cause various cancer cells to senesce (Lorenz et al , ; Vargas et al , ; Venkatesh et al , ). In the context of aging however, senescent cell reduction , rather than promotion , is desired, since senescent cells contribute to age‐related diseases (De Keizer, ).…”
Section: Hdac Inhibitors and The Hallmarks Of Agingmentioning
confidence: 99%
“…In the context of aging however, senescent cell reduction , rather than promotion , is desired, since senescent cells contribute to age‐related diseases (De Keizer, ). Importantly, the ability of HDAC inhibitors to cause cell senescence may be cancer specific; sodium butyrate was shown to potentiate senescence in human and rat glioma cell lines but not in normal astrocytes (Vargas et al , ). Furthermore, as the senescent cell state is reinforced by the chromatin state at the epigenetic level (Narita et al , ; Funayama & Ishikawa, ), there is high potential for HDAC inhibitor involvement in the phenotype.…”
Section: Hdac Inhibitors and The Hallmarks Of Agingmentioning
confidence: 99%
“…Quercetin inhibits the growth of multiple human cancer cell lines (colon, breast, lung, etc.) through demethylation, induction of HAT, inhibition of HDAC, and alteration in miRNA expression of tumor suppressor and oncogenic miRNAs (Guo et al, 2015;Lam et al, 2012;Lee, Chen, & Tseng, 2011;Tan et al, 2009;Vargas et al, 2014).…”
Section: Epigenetic Regulation Of Cancer By Phytochemicalsmentioning
confidence: 99%